Involvement of deoxyribonucleic acid polymerase III in W-reactivation in Bacillus subtilis. - Fields, P I (1980)
6-(p-Hydroxyphenylazo)-uracil, a purine analog that is known to specifically inhibit deoxyribonucleic acid polymerase III in gram-positive organisms, inhibited W-reactivation in Bacillus subtilis. On the other hand, W-reactivation proceeded normally in the presence of 6-(p-hydroxyphenylazo)-uracil when a strain possessing a resistant deoxyribonucleic acid polymerase III was used as the host.